PEMBELAJARAN MENULIS TEKS DRAMA MENGGUNAKAN MEDIA FLIPBOOK BERBASIS KOMIK PADA PESERTA DIDIK KELAS VIII SMPN 40 BANDUNG TAHUN PELAJARAN 2021/2022 - Sabila Rahmatunnisa; Titin Nurhayatin; Rendy Triandy (STKIP Subang, 2022)
This research is motivated by the low ability of students and their difficulties in writing drama texts. One of the factors that causes this is the lack of creative and innovative use of media and technology by educators. As is known, the use of media and technology in learning can increase students' interest and motivation to learn. The purpose of this research is to improve the ability of students to write drama texts according to the content, language, and structure; to describe the differences in the ability to write drama texts between the experimental class using comic-based flipbook media and the control class using image media; and to test the effectiveness of comic-based flipbook media in learning to write drama texts. The method used is a quasi-experimental method of pre-test - post-test design with a control group. The data obtained were pre-test and post-test data from the experimental and control classes of students in class VIII of SMPN 40 Bandung. The results of this study proved that the ability of students to increase in learning to write drama texts using comic-based flipbook media. This is evident from the average value of the pretest experimental class of 20.75 which increased to 86.00 at the time of the post-test. There is a significant difference in learning outcomes between the experimental and control classes, in the experimental class an average post-test of 86.00 was obtained, while the post-test average of 75.75 was obtained in the control class. Comic-based flipbook media is effectively applied in learning to write drama texts compared to image media. This is evidenced by the results of the Mann Whitney Test with a significance value of 0.000 <0.05. This proves that the comic-based flipbook media is effectively used in learning to write drama texts.